2014
DOI: 10.1111/ede.12084
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of limb transcriptional enhancers in the mouse

Abstract: Transcriptional enhancers are genomic sequences bound by transcription factors that act together with basal transcriptional machinery to regulate gene transcription. Several high-throughput methods have generated large datasets of tissue-specific enhancer sequences with putative roles in developmental processes. However, few enhancers have been deleted from the genome to determine their roles in development. To understand the roles of two enhancers active in the mouse embryonic limb bud we deleted them from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 65 publications
4
17
0
Order By: Relevance
“…(Table 1). Our results imply that conservation of at least some UCEs still is of high importance for normal phenotype, which is in accordance with published UCEs knockout studies (Dickel et al, 2018;Nolte et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…(Table 1). Our results imply that conservation of at least some UCEs still is of high importance for normal phenotype, which is in accordance with published UCEs knockout studies (Dickel et al, 2018;Nolte et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
“…Initial deletion studies suggested that the absence of UCEs did not result in overt phenotypic changes in mice (Ahituv et al, 2007). More recently, however, clear phenotypic effects were detected when other UCEs were deleted from the mouse genome (Dickel et al, 2018;Nolte et al, 2014). A large fraction of UCEs have been found to be transcriptionally active and involved in multiple human cancers (Calin et al, 2007;reviewed in Fabris and Calin, 2017;Terracciano et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, further follow-up studies found that even though deletion of ultra-conserved enhancers did not cause perinatal death, mice that survived the deletions did show signs of developmental defects after more comprehensively inspecting for phenotypic changes under different conditions. For example, deleting a conserved and Shh regulating enhancer resulted in degenerations of skeletal elements in limb bud [48] and deleting an ultra-conserved limb-developmental associated enhancer led to significantly decreased body size in mouse embryos [49]. Dickel et al showed that single enhancer deletions of three out of the four enhancers regulating the Aristaless-related homeobox (ARX/Arx) gene led to decreased overall growth or brain abnormality in transgenic mice [50].…”
Section: Plos Geneticsmentioning
confidence: 99%
“…Mutations in a CNE proximal to the HMX1 gene cause aberrant external ear development in wild populations of rats and highland cattle ( 39 ). A mouse sequence called M280 , which contains a CNE identical between human, mouse and rat, is indispensable for body growth in mice ( 40 ). Many more cases linking CNEs to both human disease and lineage-specific traits are discussed in more depth in the ‘ Diseases associated with non-coding conservation’ and ‘ CNE Modifications and Losses ’ sections.…”
Section: Known Functions Of Conserved Non-coding Elementsmentioning
confidence: 99%